Disparities in Mental Health Service Use among Racial/Ethnic Minority Elderly - Jimenez, Daniel E. (2012)
BACKGROUND/OBJECTIVES: We apply the Institute of Medicine definition of healthcare disparities to measure disparities at different junctures of episodes of mental health care and to identify disparities in types of mental health services used. DESIGN: Four two-year longitudinal datasets from Panels 9–13 (2004–2009) of the Medical Expenditure Panel Surveys were combined. SETTING: Large-scale surveys of families and individuals and their medical providers across the United States. PARTICIPANTS: A total of 1658 (981 Whites, 303 Blacks, and 374 Latinos) participants aged 60+ with probable mental health care need. MEASUREMENTS: Mental health care need was defined as Kessler-6 Scale >12 and PHQ-2 >2. Five aspects of mental health care episodes were analyzed: 1) treatment initiation; 2) adequacy of care; 3) duration of care; 4) number of visits; 5) and expenditures. We assessed whether episodes of care included only prescription drug fills, only outpatient visits, or both. RESULTS: Treatment initiation and adequacy were lower for Blacks and Latinos than Whites. Latinos experienced episodes with longer duration, increased number of visits, and more expenditures. Blacks and Latinos had significantly lower rates of episodes that consisted of only medication refills. Blacks had significantly greater rates of episodes with only outpatient care visits. Latinos had significantly higher rates of medication plus outpatient visits. CONCLUSION: Low mental health treatment initiation and poor adequacy suggest the need for culturally appropriate interventions to engage older Blacks and Latinos in mental health care. The surprising findings among Blacks (greater rates of outpatient care visits) and Latinos (higher rates of medication plus outpatient visits) highlight the complexities of the older adult population and suggest new avenues for disparities research.